Bacterial Contamination Analysis Based On Total Plate Count From Various Uses Of Compact Powder - Putri, Ni Putu Sintyani; Kristinawati, Erna; Khusuma, Ari (Poltekkes Kemenkes Mataram, 2025)
The repeated and alternating use of compact powder can increase the risk of bacterical contamination. This contamination can be harmful to the skin health of the users, especially if the compact powder used has been contamination with bacteria exceeding the standard limit set by BPOM, which is 5 × 10³ colonies/g or colonies/mL. Therefore, an analysis of bacterial contamination in the repeatedly and alternately used sompact powder from various uses is necessary using the Total Plate Cound (TPC) method to ensure the suitability and safety of the compact powder. The objective is to determine the level of bacterial contamination based on the Total Plate Cound (TPC) on compact powder used by makeup artists, tester from cosmetic stores, personal use dan new product. The samples of conpact powder analyzed amounted to 24 samples, using purposive sampling technique and the data was analyzed descriptively. The result obtained from the calculation of the average number of bacterical colonies in personal use compact powder, new product and tester from each cosmetic store are < 3 x 10¹ CFU/g, while the average for compact powders sourced from makeup artists is 1.66 x 10^5 CFU/g. Compact powder derived from personal use, new products, and those used as testers by cosmetic stores show ALT values that still fall within the category of meeting the standards set by BPOM. Meanwhile, compact powder derived from makeup artists shows ALT values that exceed the standards set by BPOM.